Tafsir QS. Al-Baqarah : 275-276: About Usury, Its Meaning and Implications for the Economy - Bukhari, Bukhari; Basri, Halimah (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
The topic of this research is usury, based on the interpretation of the riba verses in the Koran. As well as discussions about buying and selling, usury and bank interest which have implications for economic activities today. The concept of usury has a significant impact on the people's economy, including economic injustice, restrictions on productive investment, as well as its impact on sharia banking and foreign investment. Usury practices can also dampen entrepreneurship and change consumption patterns. A descriptive qualitative research approach, the data used is secondary data obtained from journal articles, books and other related information. The results of this research are that the Al-Qur'an states that buying and selling and usury are not the same, therefore usury is strictly prohibited and the prohibition of usury in Islam is based on moral and humanitarian considerations, with the aim of eliminating economic practices that give rise to oppression and tyranny (Al-Qur'an Surah Al-Baqarah 275, 275-276). However, scholars have different opinions regarding the punishment of bank interest, some believe that bank interest is absolutely haram because of the similarities between usury and bank interest. Some other scholars judge that bank interest is halal or permissible because bank interest aims to maintain the value of money, so that the borrower does not suffer. losses due to the decline in exchange rates in the next few years.